Bank loan loss accounting treatments, credit cycles and crash risk - Andreou, Panayiotis; Cooper, Ian; Louca, Christodoulos; Philip, Dennis (My University, 2017)
Banks that follow conditional conservatism in their loan loss accounting treatments benefit from a reduction in crash risk. The key discretionary loan loss accounting channels are provisions and allowances. We show that conditional conservatism reduces crash risk of small banks during periods of credit contraction and boom. Interestingly, for large banks, crash risk is not reduced by more conservative accounting even for those with higher levels of opacity. Hence regulation prompting for more conservative bank loan loss accounting does not present a significant opportunity to limit systemic effects arising from abrupt price declines in the stocks of large banks.
Keywords: Loan loss accounting; Crash risk; Accounting conservatism; Bank lending